HOW TUNE HOTEL’S PALEMBANG EMPLOYEE EXPRESS THE SPEECH ACT OF APOLOGY BOTH IN ENGLISH AND BAHASA INDONESIA - Mulyani, Destia D (Linguists : Journal of Linguistics and Language Teaching, 2018)
A good employee should have an ability to serve the customers well. By using a good language and right manner, employee can make customers feel satisfied and they wanted to return back and stayed there again. A good language followed by the right manner can be called speech act. When someone did something wrong, what would they like to do or to said.  This article focused on the way hotel employees said and acted to express their apology. The result revealed that most employees used speech act in many situations both genders had similarity in using apologizing strategies. They employed most similar categories in term of certain situations.